The wounded platoon [videorecording (DVD)] - Edge, Dan; Edge, Dan; Edge, Dan; Smith, L. Christopher (PBS Video, 2010)
"On November 30, 2007, 24-year-old Kevin Shields went out drinking with three Army buddies from Fort Carson, Colo., a base on the outskirts of Colorado Springs. A few hours later, he was dead -- shot twice in the head at close range and left by the side of the road by his fellow soldiers. Shields' murder punctuated a string of violent attacks committed by the three, who are now serving time in prison for this and other crimes, and it contributed to a startling statistic: Since the Iraq war began, a total of 17 soldiers from Fort Carson have been charged with or convicted of murder, manslaughter or attempted murder committed at home in the United States, and 36 have committed suicide. In The Wounded Platoon, Frontline investigates a single Fort Carson platoon of infantrymen -- the 3rd Platoon, Charlie Company, 1st Battalion, 506th Infantry -- and finds, after a long journey, a group of young men changed by war and battling a range of psychiatric disorders that many blame for their violent and self-destructive behavior. Since returning from Iraq, three members of the 3rd Platoon have been convicted on murder or attempted murder charges; one has been jailed for drunk driving and another for assaulting his wife; and one has attempted suicide."-- Frontline website.